A comprehensive atlas of the bonobo gut bacteriome and its associated host and exposome factors - Jonas R.R. Torfs; Mélodie Kreyer; Stijn Wittouck; Sarah Ahannach; Barbara Fruth; Sarah Lebeer; Marcel Eens; Nicky Staes (Cell Reports)
Summary: In great apes, the gut bacteriome shapes key physiological functions and is influenced by both the exposome and the host. Yet, isolating these independent contributions remains challenging. We sequenced 644 fecal samples from 212 wild and zoo-housed bonobos (Pan paniscus), matched with detailed data collection on host and exposome factors. This standardized dataset reveals clear differences in gut bacterial diversity and composition between wild and captive bonobos. Within the controlled zoo-housed cohort, factors such as age, transit time, diet, early life adversity, and medication use influence gut bacterial structure. Notably, social contact emerges as a stronger predictor of bacteriome similarity than genetics or other exposome factors, while maternal effects persist even in non-cohabiting mother-offspring dyads. By offering a unique, comprehensive, and standardized dataset, our work paves the way for future research into microbiome ecology, providing insights with far-reaching implications for both human and animal health in an increasingly industrialized world.